Clinical evaluation of different types of teeth in in-office whitening - Esteves, Lara Maria Bueno [UNESP]; Souza-Costa, Carlos Alberto [UNESP]; Honma, Cíntia Miuky [UNESP]; Aidar, Karen Milare Seicento; Fagundes, Ticiane Cestari [UNESP]; Briso, André Luiz Fraga [UNESP] (My University, 2024)
Objective: This prospective case series aimed to clinically evaluate the bleaching effect, spontaneous tooth sensitivity, and variation in the thermal sensation threshold of different groups of teeth undergoing in-office bleaching. Method and materials: Ten patients received conventional bleaching treatment: 35% hydrogen peroxide with three bleaching sessions of 45 minutes, evaluating color change (∆E and ∆E00), Whitening Index (WID), and tooth sensitivity (visual analog scale). Thermal stimulus-generating devices were used to simulate sensitivity caused by low temperatures through quantitative sensory tests. Analyses were conducted individually on different teeth groups (n = 20) (mandibular incisors, maxillary incisors, canines, maxillary first premolars). Results: Regarding color change, mandibular and maxillary incisors did not statistically differ from each other but showed significant difference and greater bleaching potential compared to canines and maxillary first premolars (P = .018). Regarding sensitivity, mandibular and maxillary incisors presented the highest spontaneous sensitivity values (P = .032), while maxillary first premolars did not display painful symptoms, also observed in provoked sensitivity analysis (P = .025). Conclusions: The general analysis of the results indicates that the tooth type affects the response to the whitening treatment, both in relation to the esthetic benefit and the occurrence of tooth sensitivity. It was observed that mandibular incisors reach the degree of chromatic saturation before canines and premolars, in addition to presenting greater bleaching sensitivity. Personalizing the treatment, based on prior knowledge of the degree of saturation, anatomical factors, and the risk of sensitivity, can provide considerable advantages in the whitening technique.
Keywords: color analysis; dentistry; hydrogen peroxide; tooth bleaching; tooth sensitivity; Whitening Index